Multiple Sclerosis - Yamout, Bassem I.; Alroughani, Raed (Seminars in Neurology, 2018)
Multiple sclerosis (MS) is a chronic central nervous system inflammatory disease of autoimmune etiology, mediated by activated T cells with evolving evidence of a significant contribution from B cells and cells of the innate immune system. The disease is thought to be due to a complex interaction between different genetic and environmental factors. The prevalence of MS is rising all over the world, due on one hand to earlier diagnosis and prolonged survival, and on the other to a true increase in incidence of the disease. The diagnosis of MS remains clinical despite recent advances in diagnostics and relies on demonstrating dissemination in space and time while excluding alternative diagnoses. The Mc Donald diagnostic criteria, with their recent 2017 revision, are currently widely accepted in the MS community. Although no cure is yet available, many disease-modifying therapies (DMTs) have shown different levels of efficacy in preventing relapses, accumulation of lesions on magnetic resonance imaging (MRI), and disability progression. Current treatment strategies include gradual escalation based on clinical and radiological criteria that determine treatment response, or initial induction with high efficacy DMTs especially in patients with an early aggressive course.
Keywords: multiple sclerosis; review; treatment guidelines; diagnosis